Strontium ranelate retards disc degradation and improves endplate and bone micro-architecture in ovariectomized rats with lumbar fusion induced – Adjacent segment disc degeneration - Qi Sun; Fang Liu; Jiakang Fang; Qiangqiang Lian; Yunpeng Hu; Xinyu Nan; Fa-Ming Tian; Guochuan Zhang; Dianwen Qi; Liu Zhang; Jingwen Zhang; Yang Luo; et al. (Bone Reports, 2024)
Objectives: Adjacent segment disc degeneration (ASDD) is one of the long-term sequelae of spinal fusion, which is more susceptible with osteoporosis. As an anti-osteoporosis drug, strontium ranelate (SR) has been reported to not only regulate bone metabolism but also cartilage matrix formation. However, it is not yet clear whether SR has a reversal or delaying effect on fusion-induced ASDD in a model of osteoporosis. Materials and methods: Fifth three-month-old female Sprague-Dawley rats that underwent L4-L5 posterolateral lumbar fusion (PLF) with spinous-process wire fixation 4 weeks after bilateral ovariectomy (OVX) surgery. Animals were administered vehicle (V) or SR (900 mg/kg/d) orally for 12 weeks post-PLF as follows: Sham+V, OVX + V, PLF + V, OVX + PLF + V, and OVX + PLF + SR. Manual palpation and X-ray were used to evaluate the state of lumbar fusion. Adjacent-segment disc was assessed by histological (VG staining and Scoring), histomorphometry (Disc Height, MVD, Calcification rate and Vascular Bud rate), immunohistochemical (Col-II, Aggrecan, MMP-13, ADAMTS-4 and Caspase-3), and mRNA analysis (ColI, Col-II, Aggrecan, MMP-13 and ADAMTS-4). Adjacent L6 vertebrae microstructures were evaluated by microcomputed tomography. Results: Manual palpation and radiographs showed clear evidence of the fused segment's immobility. After 12 weeks of PLF surgery, a fusion-induced ASDD model was established. Low bone mass caused by ovariectomy can significantly exacerbate ASDD progression. SR exerted a protective effect on adjacent segment intervertebral disc with the underlying mechanism possibly being associated with preserving bone mass to prevent spinal instability, maintaining the functional integrity of endplate vascular microstructure, and regulating matrix metabolism in the nucleus pulposus and annulus fibrosus. Discussion: Anti-osteoporosis medication SR treatments not only maintain bone mass and prevent fractures, but early intervention could also potentially delay degenerative conditions linked to osteoporosis. Taken together, our results suggested that SR might be a promising approach for the intervention of fusion-induced ASDD with osteoporosis.